Exhaustive characterization of marble to industrial applications: case of marble from the Filfila deposit (Skikda, northeast Algeria) - Aichouri, Imen; Nettour, Djamel; Chaib, Rachid; Derrardjia, Nesrine; Gherbi, Cherif; Bensehamdi, Salim; Boukhamla, Yousra (Technology audit and production reserves, 2025)
The object of this research is deals with the Filfila marble deposit of all types. The examined area is situated in the Filfila massif, a significant section of the Kabyle basement, in the inner region of the Alpine range in northeastern Algeria. Given that it has been mined for many years, this massif is especially notable for the importance of its marble reserves. There are three primary types of marble found in this deposit: mignonette marble, which is prized for its exquisite green tones; gray marble, which has delicate subtleties; and white marble, which is highly sought after due to its extreme purity. Multi-scale petrographic techniques that integrate microscopic examinations with macroscopic observations (color, texture, and structure) form the basis of the methodology employed in this work. Under plane-polarized light, thin sections of 30 µm in thickness were created in the University of Annaba’s geology lab. According to the results, the material had a uniformly large texture and was primarily composed of microcrystalline calcite. Carefully polished samples were subjected to scanning electron microscopy (SEM) analysis in order to advance the investigation. SEM was able to disclose fine microstructural characteristics, such as crystal shape, microcracks, porosity, and the distribution of mineral phases, because of its nanometric resolution, which shows a high purity of white marble in addition to the main impurities of gray marble. The mechanical characteristics and durability of the marbles were illuminated by these observations, which allowed for the identification of notable variations among them, especially with regard to the density of discontinuities and the size of the crystal grains. By combining optical and electron microscopy techniques, this integrated approach made it possible to thoroughly characterize Filfila marble by exposing its physical characteristics and mineralogical composition. The results offer a solid scientific basis for possible industrial uses and are useful reference information for upcoming comparative geological studies.